Medicaid Managed Care: Substantial Shifts In Market Landscape And Acquisitions, 2006-20 - Li, Bohan; Layton, Timothy J (Health affairs (Millwood, Va.), 2025)
There has been a significant shift in the composition of the Medicaid managed care market over the course of the past two decades. The market is consolidated among five national firms, and those firms have nearly half of all beneficiaries enrolled in managed care plans. State markets are even more consolidated, typically giving Medicaid beneficiaries only a few plan options. This article describes the Medicaid managed care market during the period 2006-20, using enrollment data and a novel data set on acquisitions. Our study found a marked decrease in the number of parent payers (unique firms that own at least one Medicaid managed care plan), despite an increase in total enrollment, as well as a high volume of acquisitions. In fact, approximately one in four plans were involved in at least one acquisition during the study period. National payers are playing an increasingly dominant role in Medicaid managed care, with both the number and the market share of local payers decreasing during the study period. Future research is needed to understand the consequences of these shifts for the level of competition in this market, state finances, and beneficiary health.